(untitled) (Research, Society and Development, 2021)
Coffee quality is influenced by several factors, including the drying conditions. Therefore, this study evaluated the influence of the relative humidity of the drying air on the quality attributes of the coffee beverage. Arabica coffee (Coffea arabica L.) fruits were selectively harvested. The samples were dried in two steps in a fixed-bed dryer at an air speed of 0.33 ms-1. In the first step, drying was performed until the water content was 0.428 g of water g of dry matter-1, without controlling the dew point temperature. The second step was performed until the water content was 0.123 g of water/g of dry matter-1, with dew point temperature control. A total of 11 treatments were tested involving nine combinations of dry bulb temperatures of 35 and 40 °C and dew point temperatures of 2.6, 10.8, 16.2 °C, plus two dryings at 35 and 40 °C dry bulb temperature without dew point temperature control. The samples were evaluated sensorially by three certified specialty coffee tasters. The data were subjected to principal component analysis. In the sensory analysis, the samples received total scores of 83.0 to 85.5 points. The drying conditions significantly influenced the quality of the coffee beverage. Drying at a dry bulb temperature of 40 °C and a dew point temperature of 16.2 °C (25% RH) is indicated for the production of higher quality coffees with a shorter drying time.